Decoding the Meaning of Tumpeng in Roland Barthes’s Semiology Perspective - Setya Ambar Pertiwi; Rudy Harjanto; Novita Damayanti; Yunita Sari; Syubhan Akib (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
This research uses Roland Barthes's theoretical framework to investigate the cultural importance of the traditional Indonesian dish, Tumpeng. In order to better comprehend this cultural artifact, this study seeks to unravel the underlying symbolic meanings and dimensions that are constructed throughout the Tumpeng tradition. It also shows how Barthes's concepts of objects, interpretations, and myths might be useful in this endeavor. It draws attention to the connections among cuisine, culture, and semiotics and emphasizes the relevance of Tumpeng as a unique expression of Indonesian cuisine. This study shows that Tumpeng functions as a potent cultural signifier within Indonesian society, representing communal identity, social hierarchy, and spirituality through an investigation of its visual and philosophical aspects. Tumpeng's aesthetic style, color scheme, and physical arrangement all convey ideas about societal norms and beliefs. Practices of Tumpeng consumption also entail several layers of interpretation, whereby personal and collective meanings are created and communicated. Further, by decoding the meaning of Tumpeng, it is hoped to comprehend the interactions between cultural artifacts, interpretation, and myth-making techniques.